Solanum nigrum Unripe fruit fraction attenuates Adriamycin resistance by down-regulating multi-drug resistance protein (Mdr)-1 through Jak-STAT pathway - Sankar Jagadeeshan; Diana David; S. Jisha; S. Manjula; S. Asha Nair (BMC, 2017)
Abstract Background Solanum nigrum, herbal plant that commonly grows in temperate climate zone, has been used as a traditional folk medicine whose ripen fruits were proven to exhibit anti-tumor properties. In traditional Chinese medicine, it has been used for centuries to cure inflammation, edema, mastitis and hepatic cancer and in the Ayurvedic system of traditional medicine in India, S. nigrum is applied against enteric diseases, ulcer, diarrhea and skin diseases. A methanolic glycosidic extract fraction of unripe fruit of S. nigrum (SNME) was investigated for its anticancer property and possible mechanism to surmount adriamycin resistance in NCI/ADR-RES cells. Methods The NCI/ADR-RES cells were treated with 7.8125, 15.625, 31.25, 62.5, 125 and 250 μg/ml of methanolic extract of S. nigrum (SNME) for 12, 24 and 48 h, to check the cell viability and proliferation. The cells were also exposed to adriamycin alone or in combination with SNME and the effects on cell growth were determined by MTT. Cell cycle analysis, Ethidium bromide and Acridine orange staining, Annexin-binding efficiency, nuclear condensation and DNA fragmentation of the apoptotic NCI/ADR-RES cells were also determined. To elucidate the relationship between SNME and multi drug resistance, we analyzed the expression levels of Mdr-1, JAK1, STAT3, and pSTAT3 in NCI/ADR-RES cells after treatment with SNME. Results Results from the cytotoxicity assay showed a direct correlation between the concentration of methanolic glycosidic extract fraction of S. nigrum (SNME) and the surviving cell population. Combination with Adriamycin, SNME exhibits a synergistic action on NCI/ADR-RES cells, giving the first line of evidence to overcoming Adriamycin resistance. The SNME mediated cell growth suppression was proven to be apoptotic, based on results obtained from DNA fragmentation, annexin V apoptosis assaay and PARP cleavage analysis. Looking into the molecular insight SNME surpasses the chemoresistance of NCI/ADR-RES cells by inhibiting the JAK-STAT3 signaling pathway through the down regulation of JAK1, STAT3, pSTAT3, and Mdr1 expression. Conclusions Collectively our findings suggest that unripe fruit of Solanum nigrum could possibly be used as a chemosensitizing agent against Adriamycin resistant cancers.